Pengaruh Content Marketing dan Electronic Word Of Mouth Terhadap Keputusan Pembelian pada Restoran Baegopa House of Hungry Kota Malang - Raniah Marwa Andhini; Mohammad Maskan; Ita Rifiani Permatasari (Indo Publishing, 2025)
In this digital era, the internet has become an integral part of the business landscape, including the culinary sector. Many culinary businesses now utilize content marketing to promote their products and increase sales. In addition to content marketing, electronic word of mouth also plays a significant role in influencing consumer purchasing decisions. Baegopa restaurant is one such business that employs both content marketing and electronic word of mouth strategies. Howerver, engagement with its online content remains relativeliy low. Therefore, this study aims to analyze content marketing and electronic word of mouth on purchasing decisions at Baegopa Restaurant in Malang City. This research was an explanatory research and employed quantitative approach. The variables studied were content marketing, electronic word of mouth, and purchasing decisions. This research used observation and questionnaire data collection techniques. With purposive sampling technique, 100 respondents were selected as consumers of Baegopa Restaurant. The data were analyzed using multiple linear regression and hypothesis testing. Based on the t-test, Content Marketing (X1) and the Electronic Word of Mouth (X2) have a partial influence on the purchasing decisions (Y). Meanwhile, the F hypothesis test shows that Content Marketing and Electronic Word of Mouth simultaneous influence on purchasing decisions. The coefficient of determination (R2) was 0.721, meaning 72.1% of the variation in purchasing decisions was explained by the two variables, while the remaining 27,9% was influnced by other factors. The results of this study, conclude that content marketing and electronic word of mouth have a significant influence on purchasing decisions at Baegopa Restaurant in Malang City. Therefore, it is recommended that Baegopa Restaurant develop content marketing strategies that are relevant to consumer needs and enhance communication effectiveness.